PENGARUH PARAMETER VARIASI ASPEK RASIO PADA ANALISIS CFD AERODINAMIKA AIRFOIL NACA 0012 - Qowim, Minhajul (Universitas Majalengka, 2023)
Indonesia, as the world's largest archipelagic country, benefits from its unique geographical conditions, making airplanes the most suitable mode of transportation. This is evident from the increasing number of airlines, a notable development in the aviation field, particularly in military aviation, is the advancement of drones or Unmanned Aerial Vehicles (UAVs). In recent years, there has been rapid technological progress in fixed-wing UAV technology. UAVs are unmanned aircraft that can be remotely controlled by pilots or capable of autonomous flight using aerodynamic principles to generate lift. Fixed-wing UAVs have wings with a fixed configuration. Unmanned aircraft offer several advantages over manned aircraft, including extended airborne endurance with efficient fuel consumption, categorized as Medium Altitude Endurance UAVs (MALE UAVs). These UAVs optimize the Lift-to-Drag ratio (CL/CD) to improve their performance. Currently, unmanned aircraft are being extensively developed for various purposes, such as exploration, reconnaissance, mining, military applications, competitions, and more.